Analisis Strategi Pemasaran Ar-Rahn Oleh Pegadaian Syariah Cabang Blauran Surabaya Dalam Meningkatkan Minat Nasabah di Masa Pandemi Covid-19 - Amaniatus Safina; Anwar, Moch. Khoirul (Universitas Negeri Surabaya, 2022)
Rahn is a pawn service product that is based on sharia principles. Ensure that in marketing the product, there are several stages of strategy which include planning, implementation, and evaluation. The purpose of this study is to find out and analyze how the marketing strategy of sharia pawn products is applied to the Pegadaian Syariah Blauran Surabaya Branch, especially during the covid-19 pandemic. This research uses descriptive qualitative method and purposive sampling technique. The results of this study conclude that the marketing strategy used by Pegadaian Blauran Surabaya Branch in increasing customer interest during the pandemic includes 3 processes, namely strategic planning, strategy implementation, and strategy evaluation. These three things are interrelated and to achieve company goals. In the planning strategy, Pegadaian Syariah Blauran Surabaya Branch plans the target market and the target market to be addressed, namely potential customers. Then in the implementation of the strategy, Pegadaian Syariah Blauran Surabaya Branch carried out a 7P marketing mix strategy, namely: product, place, price, promotion, people, physical evidence, and processes. And the last is the strategy evaluation, the Pegadaian Syariah Blauran Surabaya routinely evaluates once a month. The process of the three marketing strategies carried out by Pegadaian Syariah Blauran Surabaya Branch has been carried out well, as evidenced by a very significant increase in the number of customers from 2020-2022.